Doubled geometry and α′ corrections. Issue 4 (April 2016) - Demulder, Saskia; Gaddam, Nava; Zwiebach, Barton
Abstract : We review the construction of a duality‐invariant higher‐derivative theory based on a doubled metric. This theory incorporates the corrections needed in the Green‐Schwarz anomaly cancellation mechanism. We note recent progress in elucidating the structure of the theory. This article is largely based on the plenary talk given by B. Zwiebach at "The String Theory Universe", 21st European String Workshop, Leuven, September 7‐11, 2015.